METHODS FOR WATERLESS SEBUM REMOVAL - ZHOU, Zhangji; YE, Chengda; CHEN, Gong (2025)
Methods for waterless removal of sebum from a subject. Methods include contacting the hair of a subject with a heated airflow, for example, as generated by a device for waterless sebum removal. As the heated airflow contacts sebum, it warms and softens the sebum to facilitate removal of the sebum from the subject. Methods can make practical use of the Coandǎ effect to increase contact of the subject's hair with an absorbent substrate for transfer of heated sebum to the substrate during use. Methods can also utilize devices that include sensors and control circuitry for smart management of operation of the device, such as control of temperature of the heated airflow, to ensure efficacy of sebum removal without causing damage to the subject's hair. L'invention concerne des procédés d'élimination sans eau de sébum d'un sujet. Les procédés comprennent la mise en contact des cheveux d'un sujet avec un flux d'air chauffé, par exemple, tel que généré par un dispositif d'élimination de sébum sans eau. Lorsque le flux d'air chauffé entre en contact avec le sébum, il chauffe et ramollit le sébum pour faciliter l'élimination du sébum du sujet. Des procédés peuvent permettre une utilisation pratique de l'effet Coanda pour augmenter le contact des cheveux du sujet avec un substrat absorbant pour le transfert de sébum chauffé au substrat pendant l'utilisation. Les procédés peuvent également utiliser des dispositifs qui comprennent des capteurs et des circuits de commande pour la gestion intelligente du fonctionnement du dispositif, tels que la commande de la température du flux d'air chauffé, pour assurer l'efficacité de l'élimination du sébum sans provoquer d'endommagement des cheveux du sujet.